Implementation of Lean Services in Hospitals To Improve The Efficiency of Patient Services in The Organization Of Health Social Security (BPJS) - Suhartini Suhartini; E Yuliawati; N Rahmawati; D A H Syahputra (Institut Teknologi Sepuluh Nopember, 2018)
The hospital has a very vital role in efforts to improve the health status of all Indonesian people. When the process of serving a hospital is not effective and efficient, patients who can be referred to as customers from the hospital will feel the impact. Long processes and patients who are required to queue in each process results in patients having to wait a long time to get service. It is hoped that Lean will apply it to hospitals to improve the process so that it can provide optimal services, and at a lower cost. From the results of this study, the waste found in the service of The Organization of Health Social Security (BPJS) is waiting /delay & defect. The impact of lean service implementation on the BPJS Health patient service process according to the process activity mapping, increasing the process cycle efficiency to 64%, according to the supply chain response matrix is to add service facilities, and according to the quality filter mapping is to carry out routine control of the registration process and the amount of stock paper and printer